The Influence of Project Based Learning Model on Learning Outcome and Student's Critical Thinking - Satria, Tio Gusti; Sapriya, Sapriya; Sa'ud, Udin Syaefuddin; Riyana, Cepi; Hajani, Tri Juli; Erander, Sari (Jurnal Prima Edukasia, 2025)
Project-based learning (PjBL) is a learning model in which students are actively involved in solving a problem by applying the skills of researching, analysing, producing and presenting learning products based on real experiences. This study aims to determine the influence of the PjBL model on students' learning outcomes and critical thinking in Natural and Social Sciences (IPAS in the Indonesian context) Class IV subjects. This research adopts a quantitative approach using the quasi-experimental method. The sample consisted of students from Darussalam Natural School Islamic Integrated Elementary School in Musi Rawas, which had just implemented the independent curriculum using the PjBL model as the applied model, while the control class received the conventional treatment. In collecting data, the techniques used are written tests in the form of description questions carried out twice (pre-test and post-test) and observation. Data analysis, data processing and analysis are carried out by determining question scores, descriptive analysis, prerequisite test analysis, and inferential analysis. The research design used was a pure experimental design with two groups, the control and experimental groups. The results of this study showed that the PjBL model significantly influenced students' learning outcomes and critical thinking skills in IPAS. The findings contribute to the existing literature on PjBL and its impact on students' learning outcomes and critical thinking skills in IPAS learning.